Implementasi Intruksi Gubernur Bali tentang Keluarga Berencana di Kecamatan Banjarangkan Kabupaten Klungkung - Anak Agung Gede Meditriana Putra; I Nyoman Putu Budiartha; Indah Permatasari (Warmadewa Press, 2022)
The high and uncontrolled population growth rate will affect the decreasing level of community and family welfare. This study aims to determine the implementation of the Governor of Bali's instructions on family planning in the Banjarangkan sub-district, Klungkung regency and the effectiveness of the Bali governor's instructions on family planning in the Banjarangkan sub-district, Klungkung regency. This study uses an empirical legal research type, with data sources consisting of primary, secondary, and tertiary. Collected by conducting a literature study, and analyzed deductively and inductively. The results showed that the implementation of the instructions of the Governor of Bali regarding Krama Bali KB in Banjarangkan sub-district has not run optimally, from what the author has observed so far in the field, there are still many people who do not understand the purpose of the Krama Bali KB, the average community thinks that KB Krama Bali is a program that encourages people to have more than two children. The Governor's instructions on KB Bali have also not been effective due to economic and educational factors. In order to run effectively, the government should carry out more socialization in a number of banjars in the Banjarangkan village area.